Pelayanan Publik Edukasi Kesehatan Gigi Pada Anak Sekolah Dasar Negeri 2 Muara Dua Kota Lhokseumawe - Dewi, Risna; Syafridah, Anita; Maisyura; Fauzan, Ahmad; Maryam; Ti Aisyah (Universitas Malikussaleh, 2025)
Oral and dental health is an essential part of overall health that significantly affects children's quality of life. However, the low level of awareness and understanding among school-aged children about the importance of maintaining dental hygiene remains a challenge. This community service activity aimed to provide education and outreach on the importance of dental health through a public service approach at SD Negeri 2 Muara Dua, Lhokseumawe City. The methods used included interactive counseling sessions, demonstrations of proper toothbrushing techniques, and the distribution of educational media to students. Teachers were also involved as strategic partners to strengthen the sustainability of health education within the school environment. The results of the activity showed an increase in students’ knowledge and enthusiasm for practicing good dental hygiene, along with active participation from the school community. This initiative reflects the implementation of public administration values in promotive and preventive health services, particularly through collaboration between elementary educational institutions and community service lecturers from Universitas Malikussaleh. Dental health education at the elementary school level proves to be an effective strategy in fostering healthy habits from an early age.